Within Patient Radiological Comparative Analysis of the Performance of Two Bone Graft Extenders Utilized in Posterolateral Lumbar Fusion: A Retrospective Case Series - Stewart, Geoffrey; Gage, Gary B.; Neidert, Gary; Adkisson, Huston Davis (Frontiers in Surgery, 2016)
Two bone graft extenders differing in chemical composition were implanted contralaterally in 27 consecutive patients undergoing instrumented posterolateral lumbar fusion as standard of care. Bone marrow aspirate and autogenous bone graft were equally combined either with β-tricalcium phosphate (β-TCP) or a hybrid biomaterial (containing hyaluronic acid but lacking a calcium salt) and implanted between the transverse processes. Fusion status on each side of the vertebrae was retrospectively graded (1-5 scale) on AP planar X-ray at multiple visits as available, through approximately month 12. Additionally, consolidation or resorption since prior visit for each treatment was recorded. Sides receiving β-TCP extender showed marked resorption prior to bone consolidation during the first 6 months. By contrast, sides receiving the hybrid biomaterial containing integrated hyaluronic acid showed rapid bone consolidation by week 6-8, with maintenance of initial bone volume through month 12. Fusion grade was superior for the hybrid biomaterial, differing significantly from β-TCP at day 109 and beyond. Fusion success at >month 12 was 92.9% vs 67.9% for the hybrid biomaterial and β-TCP-treated sides, respectively. The hybrid biomaterial extender demonstrated a shortened time to fusion compared to the calcium-based graft. Mode of action has been demonstrated in the literature to differ between these compositions. Therefore, choice of synthetic biomaterial composition may significantly influence mode of action of cellular events regulating appositional bone growth.